Class Structure and Character Tables of Permutation Groups for Weakly Bound Polymer Molecules and Some Applications. - Adekola, Folahan Amoo (Obafemi Awolowo University, 2014)
Permutation and permutation-inversion groups for polymer molecules have been systematically studied. This encompasses review of the permutation and permutation-inversion groups for dimer molecules, followed by extension to trimers, tetramers and higher polymer molecules. Some formulae for determining the conjugacy classes of both the symmetric and non-symmetric polymers are presented. It has been shown that the character tables for the polymer molecules are easy to construct once the feasible operations of the appropriate monomer groups are determined.